Implikasi Karakter Pradnyan dan Purusottama Terhadap Peningkatan Hasil Belajar Agama Hindu pada Peserta Didik Utama Widyalaya Wira Dharma Palu - Trimo, Trimo (Jayapangus Press, 2025)
The application of the values of Pradnyan and Purusottama in character education is crucial for improving the learning outcomes of Hindu Religious Education. The lack of understanding of these values needs to be examined to identify effective strategies in the learning process. This study aims to analyze the extent to which the characters of Pradnyan and Purusottama have a positive impact on the learning outcomes of Hindu Religious Education among students at Utama Widyalaya Wira Dharma Palu for the academic year 2024/2025. This research uses a quantitative research method with an explanatory approach. Respondents consist of students from grades X, XI, and XII, selected randomly. Data were collected through questionnaires and academic documents, then analyzed using simple and multiple linear regression to determine the relationship between variables. The results indicate that the character of Pradnyan contributes 76.3%, while the character of Purusottama contributes 79.7% to the learning outcomes of Hindu Religious Education. Simultaneously, both variables contribute 81.1%, with the remaining percentage influenced by other factors such as the learning environment, teaching methods, and learning motivation. These findings confirm that character education plays a crucial role in shaping students' understanding and learning achievements. The application of the Pradnyan character strengthens students' ability to think critically and wisely in understanding Hindu teachings, while the Purusottama character encourages students to achieve moral and spiritual excellence. Based on these findings, it can be concluded that the application of the values of Pradnyan and Purusottama in the teaching and learning process is highly effective and has a positive impact on improving the learning outcomes of Hindu Religious Education. Therefore, the integration of character education into the Hindu Religious Education curriculum needs to be strengthened to ensure students achieve optimal learning outcomes and possess good morals and ethics in their daily lives.